AMPUTATION DUE TO COMPLICATIONS OF DIABETES: NURSING CARE PROTOCOL - Lima, Nalva Kelly Gomes de; Silva, Jessyka Chaves da; Rebouças, Cristiana Brasil de Almeida; Coura, Alexsandro Silva; Félix, Nuno Damácio de Carvalho; França, Inacia Sátiro Xavier de (Cogitare Enfermagem, 2022)
Objective: to produce and validate a Nursing care protocol for people amputated due to diabetic complications. Methods: a methodological research study conducted in Recife-PE between February 2019 and October 2020, comprising the following stages: 1) Theoretical phase: integrative literature review; 2) Production phase; 3) Validation by specialists; and 4) Validation by the target population. The Content Validity Index was used in the validation by specialists. The Agreement Index was employed in the validation by the target population. Results: the items included in the instrument permeate the following care dimensions: Biological, Psychological and Socio-educational. Validation by the evaluators was in charge of 13 specialists. The instrument presented an index of 0.94. Validation by the target population was conducted with 33 participants; all the items achieved an agreement index ≥ 80%. Conclusion: the protocol enables comprehensive and humanized care, encouraging autonomy and assisting in rehabilitation; it also allows for a reflection regarding individualization of Nursing care.